2017
DOI: 10.2147/ijgm.s145269
|View full text |Cite
|
Sign up to set email alerts
|

A survey of adult referrals to specialist attention-deficit/hyperactivity disorder clinics in Canada

Abstract: BackgroundCanadian guidelines encourage family physicians to diagnose/manage adults with uncomplicated attention-deficit/hyperactivity disorder (ADHD); specialist referral is recommended only for complex cases. This retrospective case review investigated adults referred to Canadian ADHD clinics.MethodsAdult ADHD specialists reviewed referral letters/charts of patients (aged ≥18 years and no family history/known/expressed childhood ADHD) from family physicians/psychiatrists over 2 years.ResultsData on 515 refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…A US study found that ADHD management is not increasingly undertaken by recently trained pediatric primary care providers [42] and that pediatricians who were 10 years or more in practice were more likely to report regular ADHD care [44]. Family physician surveys in Ontario and British Columbia have indicated that most primary care physicians referred patients to a specialist for the diagnosis and management of ADHD [16,[45][46][47]. Also, about 80% of family physicians in an Ontario survey responded that they wanted additional training in the management of patients with ADHD [46] and this finding is consistent with more recent Canadian studies [16,47,48].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…A US study found that ADHD management is not increasingly undertaken by recently trained pediatric primary care providers [42] and that pediatricians who were 10 years or more in practice were more likely to report regular ADHD care [44]. Family physician surveys in Ontario and British Columbia have indicated that most primary care physicians referred patients to a specialist for the diagnosis and management of ADHD [16,[45][46][47]. Also, about 80% of family physicians in an Ontario survey responded that they wanted additional training in the management of patients with ADHD [46] and this finding is consistent with more recent Canadian studies [16,47,48].…”
Section: Plos Onementioning
confidence: 99%
“…Family physician surveys in Ontario and British Columbia have indicated that most primary care physicians referred patients to a specialist for the diagnosis and management of ADHD [16,[45][46][47]. Also, about 80% of family physicians in an Ontario survey responded that they wanted additional training in the management of patients with ADHD [46] and this finding is consistent with more recent Canadian studies [16,47,48]. The increased intensity of patient visits for ADHD during the COVID-19 pandemic has highlighted the need for primary care physicians to have the necessary mental health supports in place to assist in the diagnosis and management of these patients.…”
Section: Plos Onementioning
confidence: 99%
“…По оценкам разных авторов, 67-87% детей с СДВГ имеют хотя бы одно коморбидное психическое расстройство, а 33-67% -два и более [1]. Самыми распространенными коморбидными психическим заболеваниями при СДВГ являются депрессия, биполярное, тревожные расстройства, SUD и расстройства личности.…”
Section: коморбидность при сдвгunclassified
“…в мире у детей составляет от 5 до 12% [4], встречается в 2-7 раз чаще у мальчиков [2]. Распространенность болезни у взрослых составляет от 5 [1] до 8% [4].…”
unclassified
“…In a survey of USbased HCPs in the college/university setting, only 32% of nurses reported that they were comfortable/very comfortable in recognizing ADHD symptoms in young adults, and approximately two-thirds of physicians and nurses somewhat or strongly agreed that it was difficult to diagnose ADHD in young adults [16]. HCPs in the United States may also lack confidence in prescribing treatments for adult ADHD because of a lack of experience in managing adult patients with ADHD, the presence of psychiatric comorbidities, and a reluctance to prescribe psychostimulants [17]. Similar findings are reported in studies conducted outside of the United States, with 32% of PCPs in Saudi Arabia having poor knowledge of ADHD [18] and more than 40% of psychiatrists from Turkey agreeing that adult ADHD is difficult to differentiate from other disorders [19].…”
Section: Introductionmentioning
confidence: 99%